2011
DOI: 10.1007/s12031-011-9642-z
|View full text |Cite
|
Sign up to set email alerts
|

NR4A Gene Expression Is Dynamically Regulated in the Ventral Tegmental Area Dopamine Neurons and Is Related to Expression of Dopamine Neurotransmission Genes

Abstract: The NR4A transcription factors NR4A1, NR4A2, and NR4A3 (also known as Nur77, Nurr1, and Nor1, respectively) share similar DNA-binding properties and have been implicated in regulation of dopamine neurotransmission genes. Our current hypothesis is that NR4A gene expression is regulated by dopamine neuron activity and that induction of NR4A genes will increase expression of dopamine neurotransmission genes. Eticlopride and γ-butyrolactone (GBL) were used in wild-type (+/+) and Nurr1-null heterozygous (+/−) mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 37 publications
7
30
0
Order By: Relevance
“…This idea is consistent with the fact that chronic D2 receptor antagonism with haloperidol was shown to increase Nr4a1 in the NAc core but not in the NAc shell, dorsal striatum or cortex [50]. Moreover, blocking of D2 receptors with the selective antagonist, ectolopride, increased Nr4a1 and Nr4a3 but not Nr4a2 mRNa levels in the ventral tegmental area (VTA) [10]. When taken together, these reports suggest region-specific effects of stimulation of dopamine receptors and the signal cascades that regulate Nr4a family gene transcription and, possibly, their target genes.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This idea is consistent with the fact that chronic D2 receptor antagonism with haloperidol was shown to increase Nr4a1 in the NAc core but not in the NAc shell, dorsal striatum or cortex [50]. Moreover, blocking of D2 receptors with the selective antagonist, ectolopride, increased Nr4a1 and Nr4a3 but not Nr4a2 mRNa levels in the ventral tegmental area (VTA) [10]. When taken together, these reports suggest region-specific effects of stimulation of dopamine receptors and the signal cascades that regulate Nr4a family gene transcription and, possibly, their target genes.…”
Section: Discussionsupporting
confidence: 83%
“…Specifically, McCoy et al [30] had reported that chronic METH caused significant decreases in Nr4a1 levels, with acute METH challenge causing normalization of Nr4a1 levels. Since the repeated METH injections were identical to those used in the previous study [30], the differences in the two studies are probably due to differential molecular events that might regulate Nr4a responses in the NAc and dorsal striatum [10,12,28,50]. This idea is consistent with the fact that chronic D2 receptor antagonism with haloperidol was shown to increase Nr4a1 in the NAc core but not in the NAc shell, dorsal striatum or cortex [50].…”
Section: Discussionsupporting
confidence: 52%
“…This technology is also capable of isolating small areas of tissue such as discrete nuclei or regions within the brain as shown with the isolation of the ventral tegmental area. Previous publications have demonstrated this use in brain tissue as well as to isolate pathological tissue from normal tissue 5,11 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…Based on the standard curve generated, a total of 17.3, 24.8 pg and 50.9 pg/µl was isolated from 50, 100 and 200 dopamine neurons, respectively ( Figure 10A). To measure RNA quantity with Q-PCR, a range of concentrations of whole brain RNA and RNA from the dopamine neurons were reverse transcribed and the β-actin gene was measured using Q-PCR as previously described 5 . Based on these measurements, a concentration of 3.55, 6.82 and 20.58 pg/µl was calculated from 50, 100 and 200 dopamine neurons, respectively ( Figure 10B).…”
Section: Representative Resultsmentioning
confidence: 99%
See 1 more Smart Citation